2017
DOI: 10.1590/1983-21252017v30n223rc
|View full text |Cite
|
Sign up to set email alerts
|

Sedation of Nile Tilapia With Essential Oils: Tea Tree, Clove, Eucalyptus, and Mint Oils

Abstract: -Essential oils have been extensively used in many commercial applications, one of them being anesthetics. The effect of four essential oils (tea tree, clove, eucalyptus, and mint oils) on the sedation, recovery, and behavioral stress of Nile tilapia (Oreochromis niloticus) was evaluated. The sedative solutions, prepared with essential oils and anhydrous ethanol (1:4), were used for fish management procedures at a dose of 7.4 mL L -1 in a completely randomized block design with four treatments and seven replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…The experiment consists of six rectangular glass tanks (40 x 25 x 3 cm) labeled A-F containing sixty O. niloticus fingerlings (10 fingerlings/tank), mean weight 23.13±2.43 g and mean total length 12.50±0.39 cm randomly arranged with six treatments and two replicates [16]. Each of the glass tanks was filled with 10 L of dechlorinated municipal tap water; five of the filled tanks (B-F) were inoculated with various concentrations of aqueous crude leaves extract of B. aegyptiaca and 10 mixed sex O. niloticus fingerlings were introduced into each.…”
Section: Experimental Designmentioning
confidence: 99%
“…The experiment consists of six rectangular glass tanks (40 x 25 x 3 cm) labeled A-F containing sixty O. niloticus fingerlings (10 fingerlings/tank), mean weight 23.13±2.43 g and mean total length 12.50±0.39 cm randomly arranged with six treatments and two replicates [16]. Each of the glass tanks was filled with 10 L of dechlorinated municipal tap water; five of the filled tanks (B-F) were inoculated with various concentrations of aqueous crude leaves extract of B. aegyptiaca and 10 mixed sex O. niloticus fingerlings were introduced into each.…”
Section: Experimental Designmentioning
confidence: 99%
“…Salah satu tumbuhan yang mengandung minyak atsiri adalah Melaleuca alternifolia yang biasa dikenal dengan nama minyak pohon teh (Tea Tree Oil). Menurut Rezende et al, (2017) menyatakan bahwa senyawa anestesi alami berbahan dasar minyak atsiri dari tanaman telah digunakan sebagai bahan anestesi tradisional untuk kegiatan transportasi ikan, dikarenakan bahan tersebut tidak berbahaya bagi lingkungan dan tidak menimbulkan resiko kesehatan bagi pembudidaya. Oleh karena itu, penelitian ini dilakukan untuk mengetahui pengaruh anestesi Tea Tree Oil terhadap waktu induktif, waktu sedative , kelulushhidupan (SR) dan profil dalam darah pada ikan mas (Cyprinus carpio).…”
Section: Pendahuluanunclassified
“…In our study, it could be said that concentrations 10, 20 and 30 mg/l of mint oil may used safely for zebrafish and thereby ornemantal fishes. However, Rezende et al (2017) observed that mint oil anesthesia should not be recommended for sedation and handling due to their adverse effects on behaviors. On the other hand, Spanghero et al, (2019) reported that 80mg/l peppermint oil has an anesthetic effect on silver cat-fish.…”
Section: Anesthesia Dosesmentioning
confidence: 99%